Weakly $θ b(Λ,p)$-open Functions and Weakly $θ b(Λ,p)$-closed Functions (European Journal of Pure and Applied Mathematics, 2024)
This article is concerned with the concepts of weakly $θ b(Λ,p)$-open functionsand weakly $θ b(Λ,p)$-closed functions. Moreover, some characterizations of weakly $θ b(Λ,p)$-open functions and weakly $θ b(Λ,p)$-closed functions are established.
Keywords: Weakly θb(Λ, p)-open function; weakly θb(Λ, p)-closed function